2022
DOI: 10.3386/w30767
|View full text |Cite
|
Sign up to set email alerts
|

Racial Concordance and the Quality of Medical Care: Evidence from the Military

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In an unequal society, it may be that belonging to a privileged sociodemographic group acts as a valued resource; thus, homophily can counterbalance the power differential created by asymmetry in this resource. For example, our findings shed light on why race and/or gender concordance between educator and student influences learning outcomes (41), why that between judge and defendant affects trial outcomes (42,43), and why that between doctors and patients (even on occupation) improves health outcomes (44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 92%
“…In an unequal society, it may be that belonging to a privileged sociodemographic group acts as a valued resource; thus, homophily can counterbalance the power differential created by asymmetry in this resource. For example, our findings shed light on why race and/or gender concordance between educator and student influences learning outcomes (41), why that between judge and defendant affects trial outcomes (42,43), and why that between doctors and patients (even on occupation) improves health outcomes (44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 92%
“…Some recent work suggests these questions may be worth exploring: Kosse et al (2020) present evidence that matching mentors and mentees based on gender and socio-economic factors leads to improved outcomes in a mentorship program designed to enhance prosocial behavior in Germany. Research from health economics also provides some support for these hypotheses (Alsan et al, 2019;Frakes and Gruber, 2022).…”
Section: -Conclusionmentioning
confidence: 90%
“…Physicians from concordant racial and ethnic groups may improve trust and health engagement with preventative care and thus reduce premature mortality in populations that have faced structural barriers to health care access and treatment. 68 For instance, a recent study demonstrated that for every 10% increase in the number of black primary care physicians, the life expectancy of black individuals increased by one month. 69 Diversity in the health care professions also facilitates access to health care for underserved minorities, 70 with minority health professionals demonstrating higher likelihood to serve in high rates of uninsured and areas of under-represented racial and ethnic groups.…”
Section: The Legal Landscape and Implications To Diversity-promoting ...mentioning
confidence: 99%